A Review of Recent Developments in Turner Syndrome Research - Allen C. Huang (MDPI AG, 2021)
Turner syndrome is a rare disorder resulting from complete or partial loss of the second sex chromosome. Common manifestations include delayed growth, premature ovarian failure, congenital heart defects, endocrine disorders, lymphedema, and webbed neck. People with Turner syndrome have significantly increased mortality risk primarily due to cardiovascular abnormalities. The mechanisms that lead to these defects are not completely understood and are obscured by the significant variability of both karyotype and phenotype without consistent correlation between the two. This paper presents a review of the recent literature surrounding the symptoms, mechanisms, diagnosis, and treatment of Turner syndrome with a focus on cardiovascular manifestations. With technological advancements in genetics, the molecular processes of Turner syndrome have begun to be dissected. Certain genes on the X chromosome that typically escape inactivation have been implicated in both specific manifestations and broader risk categories. Recently identified genome-wide epigenetic changes may help explain the variability in presentation. It remains unclear as to how the combination of these factors results in the overall clinical picture, but advances in genomic, genetic, epigenetic, and -omics technology hold promise for providing insights that will improve the medical management of individuals with Turner syndrome.